(untitled) (Port Harcourt Medical Journal, 2019)
Background: Uterine rupture is a major obstetric emergency and an important cause of maternal and perinatal morbidity and mortality. Aim: To determine the prevalence, clinical presentation, management options and pregnancy outcomes following uterine rupture. Methods: It is a 5-year, descriptive, retrospective study of parturients who had uterine rupture between 1 January 2011 and 31 December, 2015, at Federal Medical Centre, Bida, North Central Nigeria. The case files of all parturients who had uterine rupture during this period were retrieved from the Medical Records department, and relevant information including maternal age, risk factors for uterine rupture, presenting symptoms, site of rupture and the definitive treatment as well as maternal and neonatal outcome using a data collection sheet was entered into a computer with SPSS version 20.0, which was also used for the analysis. Results: The prevalence of uterine rupture was 1 in 202 deliveries (48/9,718); of these, 24 (50.0%) were aged 36–40 years and 28 (58.3%) were grandmultipara (parity ≥5); 42 (87.5%) cases had previous uterine scar, whereas 15 (31.3%) had labour augmentation with oxytocin while attempting vaginal birth after caesarean section. The common presenting complaints were intrapartum vaginal bleeding (24; 50%) and abdominal pain (10; 20.8%). The most common site of rupture was anterolateral (24; 50.0%), while the most common surgical intervention was uterine repair with bilateral tubal ligation (30; 62.5%). The case fatality rate was 18.8% (9/48), neonatal survival rate was 12.5% (6/48) and perinatal mortality rate was 875/1000 deliveries (42/48). Conclusion: Uterine rupture remains an important cause of poor pregnancy outcomes in low-income settings. Previous caesarean delivery is the most common risk factor; women attempting vaginal birth after caesarean delivery should be managed by skilled health personnel in facilities with provision for emergency surgical intervention.